Who gets admitted to the Chest Pain Unit (CPU) and how do we manage them? Improving the use of the CPU in Waikato DHB, New Zealand. Issue 1 (11th February 2015) - Jade, Judith; Huggan, Paul; Stephenson, Douglas
Abstract: Chest pain is a commonly encountered presentation in the emergency department (ED). The chest pain unit at Waikato DHB is designed for patients with likely stable angina, who are at low risk of acute coronary syndrome (ACS), with a normal ECG and Troponin T, who have a history which is highly suggestive of coronary artery disease (CAD). Two issues were identified with patient care on the unit (1) the number of inappropriate admissions and (2) the number of inappropriate exercise tolerance tests. A baseline study showed that 73% of admissions did not fulfil the criteria and the majority of patients (72%) had an exercise tolerance test (ETT) irrespective of clinical picture. We delivered educational presentations to key stakeholders and the implementation of a new fast track chest pain pathway for discharging patients directly from the ED. There was an improvement in the number of patients inappropriately admitted, which fell to 61%. However, the number of inappropriate ETTs did not decrease, and were still performed on 76.9% of patients.